Intracellular miRNA or siRNA delivery and function. (September 2018) - Zhdanov, Vladimir P.
Highlights: Intracellular RNA delivery by nanoparticles is of interest for therapy. Here, the focus is on theoretical aspects of miRNA or siRNA function after delivery. Likely subsequent transient kinetics of gene expression are shown. The analysis includes various types of regulation of gene transcription. Abstract: Nanocarrier-mediated delivery and release of short non-coding RNA (e.g., miRNA or siRNA) into the cells with subsequent suppression of the populations of some of the mRNAs and proteins is of interest in the context of the development of a new generation of drugs. Bearing in mind such applications, the author shows the specifics of the corresponding transient kinetics by using three generic models without and with feedback resulting in bistability in the gene expression. In the absence of feedback, the suppression of the mRNA and protein population is transient. In the case of bistable kinetics, non-coding RNA can induce transition from the initial steady state to another steady state. The duration of this transition can be much longer than the time scale characterizing the drop of the non-coding RNA population. Quantitatively, the effect of the delivered non-coding RNA on gene expression can be appreciable if the maximum non-coding RNA population in the cytoplasm is comparable to or above 1000. All these conclusions have been drawn on the basis of calculations performed with the kinetic parameters typical for human cells.